Russian isolates enlarge the known geographic diversity of Francisella tularensis subsp. mediasiatica. - Vitalii Timofeev; Irina Bakhteeva; Galina Titareva; Pavel Kopylov; David Christiany; Alexander Mokrievich; Ivan Dyatlov; Gilles Vergnaud (PLoS ONE)
Francisella tularensis, a small Gram-negative bacterium, is capable of infecting a wide range of animals, including humans, and causes a plague-like disease called tularemia-a highly contagious disease with a high mortality rate. Because of these characteristics, F. tularensis is considered a potential agent of biological terrorism. Currently, F. tularensis is divided into four subspecies, which differ in their virulence and geographic distribution. Two of them, subsp. tularensis (primarily found in North America) and subsp. holarctica (widespread across the Northern Hemisphere), are responsible for tularemia in humans. Subsp. novicida is almost avirulent in humans. The fourth subspecies, subsp. mediasiatica, is the least studied because of its limited distribution and impact in human health. It is found only in sparsely populated regions of Central Asia. In this report, we describe the first focus of naturally circulating F. tularensis subsp. mediasiatica in Russia. We isolated and characterized 18 strains of this subspecies in the Altai region. All strains were highly virulent in mice. The virulence of subsp. mediasiatica in a vaccinated mouse model is intermediate between that of subsp. tularensis and subsp. holarctica. Based on a multiple-locus variable number tandem repeat analysis (MLVA), we show that the Altaic population of F. tularensis subsp. mediasiatica is genetically distinct from the classical Central Asian population, and probably is endemic to Southern Siberia. We propose to subdivide the mediasiatica subspecies into three phylogeographic groups, M.I, M.II and M.III.